An appraisal of Al-Ijarah Al-Mawsufah Fi Al-Dhimmah (forward ijarah) from fiqh perspective - Mohammad Monawer, A.T. (2012)
Al-IjÉrah Al-MawÎËfah FÊ Al-Dhimmah (forward ijÉrah) is a new form of transactions introduced to the Islamic banking industry which has original ground in the classical books of Islamic Jurisprudence. Most of the classical scholars discussed it with particularized ijÉrah in parallel without any separation of chapters or headings unlike al-BahËtÊ and al-MinhÉjÊ. The scholars of four schools of Islamic Law are unanimously agreed on the legality of forward ijÉrah albeit some contemporary scholars mention the early dispute in this regard and attribute prohibition of forward ijÉrah to ×anafÊ School. This attribution is not accurate as it is proved by their many classical texts. Forward ijÉrah could be more flexible for both customers and banks to the extent that it does not become void if the stipulated usufruct damages while particularized ijÉrah becomes void because of damage of the object. Therefore, there is a need for further research in this regard in order to innovate some new tools that can improve the services of Islamic financial intuitions.